Euro area government bonds – Fragmentation and contagion during the sovereign debt crisis. (February 2017) - Ehrmann, Michael; Fratzscher, Marcel
Highlights: We study the integration of sovereign bond markets during the European debt crisis. Bond markets saw a substantial fragmentation from 2010 onward. Flight to quality during the crisis largely disappeared after the ECB's OMT. This suggests that countries have been effectively ring-fenced. Italy and Spain jointly saw a reduction in yields after the OMT announcement. Abstract: The paper analyzes the integration of euro area sovereign bond markets during the European sovereign debt crisis. It tests for contagion (i.e., an intensification in the transmission of shocks across countries), fragmentation (a reduction in spillovers) and flight-to-quality patterns, exploiting the heteroskedasticity of intraday changes in bond yields for identification. The paper finds that euro area government bond markets were well integrated prior to the crisis, but saw a substantial fragmentation from 2010 onward. Flight to quality was present at the height of the crisis, but has largely dissipated after the European Central Bank's (ECB's) announcement of its Outright Monetary Transactions (OMT) program in 2012. At the same time, Italy and Spain became more interdependent after the OMT announcement, providing our only evidence of contagion. This suggests that countries have been effectively ring-fenced, and Italy and Spain benefited from the joint reduction in yields following the OMT announcement.